2020
DOI: 10.26719/emhj.19.097
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the burden on family carers of patients on haemodialysis in Jordan

Abstract: In Jordan, the number of people with end-stage renal disease who receive dialysis in 2016 increased to 5130 (1). Most of these people (5048, 98%) received haemodialysis and 2% received peritoneal dialysis (1). However, the number of sessions a week varied between patients: 2% received treatment four times a week, 71% received treatment three times a week, 26% twice a week and 1% once a week, with the average duration of the treatment session being about four hours (1). Therefore, family members, including spou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This can be explained by highly perceived task difficulty by the caregiver, shortage of medical treatment/nursing services and transportation [32], plus the mandatory sticking to dietary restrictions and lifestyle behaviors affecting the family and social life flow. Also, nephrology team rely on the parents on the daily management of the patient at home, plus having to travel for long distance to attend the weekly clinic visits and dialysis sessions and having to cover some costs of unanticipated management obligations [33]. This is similar to a study that found that 69.4% of caregiver mothers reported feeling pain in the body among which 2.10% had moderate level of burden, whereas a high prevalence of moderate to severe depression and anxiety were reported in (18.4%) and anxiety (47%) of the caregivers respectively [34].…”
Section: Comparison Of Rate Of Depression and Psychological Burden Ammentioning
confidence: 99%
“…This can be explained by highly perceived task difficulty by the caregiver, shortage of medical treatment/nursing services and transportation [32], plus the mandatory sticking to dietary restrictions and lifestyle behaviors affecting the family and social life flow. Also, nephrology team rely on the parents on the daily management of the patient at home, plus having to travel for long distance to attend the weekly clinic visits and dialysis sessions and having to cover some costs of unanticipated management obligations [33]. This is similar to a study that found that 69.4% of caregiver mothers reported feeling pain in the body among which 2.10% had moderate level of burden, whereas a high prevalence of moderate to severe depression and anxiety were reported in (18.4%) and anxiety (47%) of the caregivers respectively [34].…”
Section: Comparison Of Rate Of Depression and Psychological Burden Ammentioning
confidence: 99%
“…The urgency of addressing the issue of caregiver burden has been highlighted by studies conducted in both high-income countries like the USA and lower to middle-income countries like Turkey, Vietnam, Jordon, India, China Nigeria 8 15–22. Factors that contribute to caregiver burden may be categorised into patient-related and caregiver-related factors.…”
Section: Introductionmentioning
confidence: 99%